A framework for FFT-based homogenization on anisotropic lattices. (1st July 2018) - Bergmann, Ronny; Merkert, Dennis
Abstract: In order to take structural anisotropies of a given composite and different shapes of its unit cell into account, we generalize the basic scheme in homogenization by Moulinec and Suquet to arbitrary sampling lattices and tilings of the d -dimensional Euclidean space. We employ a Fourier transform for these lattices by introducing the corresponding set of sample points, the so called pattern, and its frequency set, the generating set. The pattern and the generating set represent the anisotropy of both the shape of the unit cell and the chosen preferences in certain sampling directions. In several cases, this Fourier transform is of lower dimension than the space itself. For the so called rank-1-lattices it reduces to a one-dimensional Fourier transform having the same leading coefficient as the fastest Fourier transform implementation available. We illustrate the results using the generalized basic scheme on an anisotropic laminate and on a generalized ellipsoidal Hashin structure. For both we give an analytical solution to the elasticity problem, in two- and three dimensions, respectively. We then illustrate the possibilities of choosing a pattern. Compared to classical grids this introduces both a reduction of computation time and a reduced error of the numerical method. It also allows for anisotropic subsampling, i.e. choosing a sub lattice of a pixel or voxel grid based on anisotropy information of the material at hand.